The urgency of addressing zoonotic diseases surveillance: Potential opportunities considering One Health approaches and common European Data Spaces - Nicola Riccetti; Serena Signorelli; Angela Fanelli; Emanuele Massaro; Manlio Bacco; Wojciech Szewczyk; Dolores Ibarreta; Juan Carlos Ciscar; Alessandro Cescatti; Sandra Coecke; Ilaria Capua (Data in Brief)
Currently, transdisciplinary data from animal surveillance that are available for One Health approaches to public health are scarce, negatively impacting our ability to anticipate and prepare for future public health threats, particularly those involving zoonotic diseases with pandemic or epidemic potential. In this article, we explore the potential of the common European Data Spaces framework to enhance the availability of animal surveillance data, in order to better address public health threats. We propose building upon and expanding existing initiatives, such as the European Data Spaces for Health, Agriculture, and Green Deal, to design innovative services. These services could enable the integration of different data sources to inform research and policymaking on public health interventions. An overarching layer, populated with data and generating integrative information, could support a One Health approach to research and policymaking for the preparedness and anticipation of zoonotic diseases. Consequently, this approach might foster data sharing from Member States by leveraging existing developments within data spaces in terms of, for example, data security. It could also support researchers and developers in accessing transdisciplinary, stratified, and quality-controlled data for their projects.